Faktor-Faktor Yang Mempengaruhi Sisa Hasil Usaha Koperasi Simpan Pinjam di Kecamatan Kuta Utara Kabupaten Badung - Sumita Dewik, Ni Kadek; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
This study aimed to determine the effect of simultaneous and partial number of members (X1), the amount of deposits (X2), the amount of the loan (X3) and working capital (X4) against Time Results of Operations of Credit Unions in the District of North Kuta Badung (Y). This research are using secondary data.. The data was collected by study case’s method. Data processed by multiple linear regression analysis. The test results obtained of the results of the number of members, the number of deposits, the amount of working capital loans have significant effect simultaneously on Business Profits Credit Unions in the District of North Kuta Badung regency. In partial results of the number of members, the number of loans and working capital have positive and significant impact on the rest of the Results of Operations of Credit Unions in the District of North Kuta Badung regency. While the variable amount of deposits a significant negative effect on the rest of the Results of Operations of Credit Unions in the District of North Kuta Badung regency.
Keywords: Time Results of Operations; the number of members; the number of deposits; the amount of the loan; capital